2020
DOI: 10.1007/s10888-020-09467-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental time restrictions and the cost of children: insights from a survey among mothers

Abstract: An important aspect when analyzing economic inequality between households with children is time. At given monetary incomes, the material well-being of families may be very different depending on how much time parents have at their disposal. In this paper, we provide estimates of the subjectively perceived cost of children depending on the extent of parental time restrictions. Building on a study by Koulovatianos, Schröder and Schmidt (J. Bus. Econ. Stat. 27:42–51, 2009) that introduces a novel way of using sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For example, 20.1% of low-PIR women have PHQ scale ≥10 in comparison with 12.0% of medium-PIR and 5.0% of high-PIR groups. As reported by prior studies, the higher incidence of depression may be because of the social isolation [ 35 ] caused by low income that exacerbated the risk of developing depressive symptoms, or by lower access to mental health services either because of living in areas with low access, having socioeconomic disadvantages, in [ 14 ] lack of health insurance coverage, or the inability to pay the cost of treatment. Comparing the classes of depression showed that the low-PIR population more likely to have ‘moderate’ and ‘moderate-severe’ depression, it prioritizes need for immediate attention for these population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 20.1% of low-PIR women have PHQ scale ≥10 in comparison with 12.0% of medium-PIR and 5.0% of high-PIR groups. As reported by prior studies, the higher incidence of depression may be because of the social isolation [ 35 ] caused by low income that exacerbated the risk of developing depressive symptoms, or by lower access to mental health services either because of living in areas with low access, having socioeconomic disadvantages, in [ 14 ] lack of health insurance coverage, or the inability to pay the cost of treatment. Comparing the classes of depression showed that the low-PIR population more likely to have ‘moderate’ and ‘moderate-severe’ depression, it prioritizes need for immediate attention for these population.…”
Section: Discussionmentioning
confidence: 99%
“…Depression among women may be linked to the Cumulative Disadvantage theory, which posits that individuals who have had an early advantage in life will accrue advantage as they age, while individuals who have lived at a disadvantage early in life will experience worse health outcomes, including depression, as they age [ 12 ]. Women are also disproportionately more likely to be primary caregivers (66% of women), in [ 13 ] which has been linked to lost income and time, and lack of health insurance [ 14 ]. Access to insurance can also play a pivotal role in treatment, as all adults with mental illnesses who were enrolled in health plans through employers spent an average of $1347 for out-of-pocket services, while adults without mental health illnesses spent $671 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 18.5% of adults aged 18 and over have reported experiencing any symptoms of depression in 2019, 1 with higher prevalence observed among low-income African American (AA) women. 2 – 6 Several factors have been proposed as contributors to this phenomenon, including residence in environments with higher poverty, 7 lower access to healthy foods, 8 lower access to mental health providers due to lack of health insurance, 9 11 higher prevalence of comorbidities, 12 14 and a lower rate of social supports. 15 The promotion and adherence to cultural beliefs such as the “strong Black woman” trope 16 18 may limit some AA women’s emotional capacity to employ healthy coping strategies that are supportive of their mental health, including seeking care for psychological issues or availing themselves of support from members of their social networks.…”
Section: Introductionmentioning
confidence: 99%